INDONESIAâS ROLE IN THE INDIAN OCEAN REGION COOPERATION: POST-IORA CHAIRMANSHIP STRATEGIES - Putri, Briliantina (Jurnal Indonesia Emas PPI Dunia, 2018)
The Global Maritime Fulcrum (GMF) vision announced by President Joko Widodo in 2014 marked a new orientation on how Indonesia see its maritime strategic environment. Indonesia has for many years focused on the Asia Pacific because the region is more conducive for trade liberalization and economic integration. The GMF requires Indonesia to look beyond Asia Pacific and give more attention to the Indian Ocean region. Indonesia has been an active member of the Indian Ocean Rim Association (IORA), a regional forum that seek to enhance economic cooperation in the Indian Ocean region. This paper explains the importance of IORA cooperation for Indonesia, its relevance to the GMF vision, and Indonesiaâs contribution to the IORA during its Chairmanship from 2015 to 2017. It argues that during the Chairmanship, Indonesia has given more weight to IORAâs geopolitical significance in two ways: normative-ideational and institutional initiatives. This paper also recommends three post-chairmanship strategies that Indonesia can continue to pursue: norms building, institutional building and capacity building. These initiatives are important to provide stronger platform for IORAâs development. A successful IORA cooperation will eventually support Indonesia to realize the GMF goals, particularly in its effort to strengthen Indonesiaâs position and presence in the Indian Ocean region.